DDIT3 regulates cementoblast mineralization by isocitrate dehydrogenase 1 through nuclear factor‐κB pathway. Issue 7 (29th November 2018) - Liu, Xiayi; Sun, Hualing; Yu, Miao; Liu, Jie; Yang, Beining; Wu, Yanru; Wang, Jiawei
Abstract: DDIT3 is of great importance in endoplasmic reticulum stress and is involved in many inflammatory diseases and mineralization processes. The cementum protects teeth from periodontitis and provides attachment for Sharpey's fibers of the periodontal ligament. However, the effect of DDIT3 on cementoblast differentiation remains largely unknown. In this study, we found that DDIT3 was suppressed during cementoblast differentiation. Knockdown of DDIT3 increased the messenger RNA (mRNA) and protein levels of several key osteogenic markers in vitro, including alkaline phosphatase, runt‐related transcription factor 2, and osteocalcin (OCN). In addition, isocitrate dehydrogenase 1 (IDH1) was increased during cementoblast differentiation, and knockdown of DDIT3 increased the protein and mRNA levels of IDH1. Furthermore, inhibition of IDH1 could partially reduce the effect of DDIT3 on cementoblast differentiation. The DDIT3 knockdown activated nuclear factor‐κB (NF‐κB) transcriptional activity and upregulated the expression of p‐p65 and p‐IκBα. The increased osteogenic differentiation ability and IDH1 expression, as induced by the DDIT3 knockdown, could be partially turned over by the addition of NF‐κB inhibitor BAY 11–7082. Overall, our data clarified that DDIT3 suppresses cementoblast differentiation through IDH1, via the NF‐κB pathway. Abstract : In this study, we reported the decreased expression of DDIT3 during cementogenic mineralization, as well as the inhibitory effect of DDIT3 to cementogenic mineralization. In addition, we showed that DDIT3 can regulate isocitrate dehydrogenase 1 through the nuclear factor‐κB pathway.